Feminist Standpoint in Giving Meaning to Symbolic Experiences in Trans-Women Discrimination - Neny Ismaya Rahayu WERDAYANTI; Alo LILIWERI; Fahruddin FAIZ (International Journal of Environmental, Sustainability, and Social Science, 2023)
The construction of gender in the social environment is closely related to external sex. Transwomen and women as entities that are symbols in representing equality in society with a patriarchal cultural system. Social construction in a patriarchal society that forms gender based on external sex, so that women's gender is seen as different from transgender women so as to provide deeper discrimination against women. Feminist standpoint sees that through marginalized groups will get a more objective view of the dominating group. Transgender women are placed as a strong objectivity to obtain how the social environment views and the discrimination they experience. The feminist movement that struggles for equality has various considerations to be able to build a perspective on the existence of transgender women and women equally. Standpoint as a result of giving meaning to the symbolic reality that shapes the experience of each individual, including the symbolic transwomen in the social environment.